Incorporating interactive demonstration applets into the mathematics classroom - Hertz, Kathleen (My University, 2012)
Recognizing that the incorporation of technology into the modern mathematics classroom often falls far behind the ideal, the author outlines the history and reasons for the delay and lists some of the difficulties and concerns with the full implementation of technology in the classroom. She then conducts an exploration of the types of technology that are available for use in the classroom. This is followed up with a brief investigation of web-based technology types and a description of their strengths and weaknesses. The author then highlights research supporting the use of these technologies and the benefits for learning that they can provide. After identifying a digital library of dynamic visualization applets designed by teachers for use in the classroom, the Wolfram Demonstrations Project (Wolfram, 2012a), the author conducts an in-depth search of the website. The author uses this online digital library to construct a catalog of applets suitable for use in basic developmental college mathematics courses, as well as for intermediate and college algebra. The author gives descriptions of these applets, lists the courses that they might be suitable for, and rates the applets as to appropriateness, accuracy, interactivity, clarity, and ability to enhance understanding. She includes these findings along with a discussion as to the strengths and weaknesses of the different types of applications. Along with suggestions for uses of the applications in the classroom, the author also offers several lesson plans that incorporate inquiry-based and constructivist methods in order to utilize the applets in a classroom situation in a format recommended to optimize learning benefits for the students.
Plan B Paper. 2012. Master of Science in Education-Secondary Mathematics--University of Wisconsin-River Falls. Mathematics Department. ii + 108 leaves. Includes bibliographical references (leaves 94-98).
Keywords: Applets; Computer-assisted instruction; Mathematics--Study and teaching (Higher)--Computer-assisted instruction; Wolfram Demonstrations Project; Mathematics--Study and teaching (Higher)